Subclinical Ketosis on Dairy Cows in Transition Period in Farms with Contrasting Butyric Acid Contents in Silages. (25th November 2014) - Vicente, Fernando; Rodríguez, María Luisa; Martínez-Fernández, Adela; Soldado, Ana; Argamentería, Alejandro; Peláez, Mario; de la Roza-Delgado, Begoña
Abstract : This study examines the relationship between subclinical ketosis (SCK) in dairy cows and the butyric acid content of the silage used in their feeding. Twenty commercial farms were monitored over a period of 12 months. The feed at each farm and the silages used in its ration were sampled monthly for proximal analysis and for volatile fatty acid analysis. A total of 2857 urine samples were taken from 1112 cows to examine the ketonuria from about 30 days prepartum to 100 postpartum. Wide variation was recorded in the quality of silages used in the preparation of diets. Approximately 80% of the urine samples analyzed had no detectable ketone bodies, 16% returned values indicative of slight SCK, and the remainder, 4%, showed symptoms of ketosis. Most of the cases of hyperkenuria were associated with the butyric acid content of the silage used (r 2 = 0.56 ;P < 0.05 ). As the metabolizable energy content of the feed was similar, no relationship was observed between the proportion of cows with SCK and the energy content of the feed. In our study, the probability of dairy cows suffering SCK is higher when they are eating feed made from silage with a high butyric acid content (35.2 g/kg DM intake).